372 Selecting Goats for Juniper Consumption Increases Pentobarbital-Induced Sleep Time. (21st September 2022) - Walker, John; Shoemake, Brian; Quadros, Danilo G; Thorne, Jacob W; Cahill, Noah
Abstract: A sodium pentobarbital-induced sleep time (ST) study was conducted on intact males, Boer x Spanish goats (n = 30), selected for high (J+) or low juniper (J-) consumption with the objective to compare the Phase I detoxification system of the genetic divergent lines (EBV of 13.1 ± 0.2 and -14.2 ± 0.3, respectively). The ST study was conducted following a minimum period of 21 days on three different diets: grazing juniper infested rangeland (JIR), forage diet with no monoterpenes (M0), and forage diet with 8 g/kg added camphor, sabinene, and α-pinene monoterpenes in a ratio of 5:4:1 (M+). Fecal samples from goats on the JIR and M+ diets were analyzed for camphor and sabinene, and, when on the JIR diet, analyzed for percentage juniper in the diet using previously developed NIRS calibrations. Data were submitted to ANOVA analysis with repeated measures, assuming as significant when alpha was less than 10% (P < 0.10) by the F test. Percentage of juniper in the diet of J+ goats on JIP (38.6 ± 3.4%) was greater (P < 0.001) than J- goats (28.0 ± 3.8%). The J+ goats slept 15.1 (P = 0.02), 14.3 (P = 0.06), and 15.8 (P = 0.06) minutes longer than J- goats on JIR, M0, and M+ diets, respectively. There was no difference in ST between diets, and there was no interaction line × diet. Goats from the J+ line had higher concentrations of camphor in their feces on the JIR (P = 0.07) and M+ (P = 0.09) diets, while sabinene concentration was similar. Goats selected for juniper consumption had longer ST than J- goats which indicates a less efficient Phase I detoxification system, probably because there were less monoterpenes in the blood to be metabolized in the liver by the cytochromes P450 enzymes.